Myopia control efficacy of second-generation defocus incorporated multiple segments spectacle lenses on fast progressing myopes: Study protocol of a randomised controlled trial - Ying Hon; Rachel Ka Man Chun; Tsz Wing Leung; Hua Qi; Keigo Hasegawa; Ka Yan Leung; Chi Ho To; Carly Siu Yin Lam; Dennis Yan-Yin Tse (PLoS ONE, 2025)
Background Spectacle-based interventions for myopia control are appealing to parents and children due to their non-invasive nature. However, long-term efficacy results remain modest and do not account for high-risk children with early-onset myopia and fast progression. This paper presents the protocol of a trial designed to evaluate the efficacy of the new-generation Defocus Incorporated Multiple Segments (DIMS) spectacle lenses in slowing the progression of myopia in children with early-onset and fast myopia progression. Methods and design This is a prospective, double-masked, active-controlled, randomised trial (ClinicalTrials.gov identifiers: NCT05888792 and NCT05888805). Participants are Chinese schoolchildren aged 4–12 years with myopia of at least −0.75 diopter (D) in both eyes and with fast progression (≥ 0.50 D per year) or fast axial growth (≥ 0.27 mm per year) in either or both eyes. They are age-stratified and randomly assigned to an experimental arm, a control arm or an auxiliary arm in a 1:1:1 ratio. The experimental arm receives new-generation DIMS spectacle lenses, while the control arm receives single-vision spectacle lenses. The control subjects will crossover to experimental lenses at the end of the first year, and all subjects will continue wearing experimental lenses in the second year. The auxiliary arm receives marketed DIMS spectacle lenses for two years. The primary and secondary outcome measures are the changes in cycloplegic objective refraction and axial length at 12 months from baseline. Peripheral refraction and choroidal thickness will also be monitored, and their relationships with myopia control efficacy will be explored. Discussion This study will provide insights into the efficacy of a new generation of DIMS technology for controlling myopia in children with early-onset and fast myopia progression, offering evidence-based practice for myopia management. Trial registration ClinicalTrials.gov identifiers: NCT05888792 and NCT05888805